2016
DOI: 10.1123/jtpe.2015-0162
|View full text |Cite
|
Sign up to set email alerts
|

Standards-Based Assessment, Grading, and Professional Development of California Middle School Physical Education Teachers

Abstract: Purpose:This study examined California middle school physical education teachers’ (grades 6–8) use of assessments based on state standards to grade their students.Methods:An electronic survey was used to collect data.Results:Of the 309 teachers surveyed, 74% based their assessments on the state physical education standards. Teachers who used standards-based assessments were more prone to assigning higher percentages of students’ grades to achievement-based assessments (e.g., skills testing, fitness, standards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 0 publications
1
9
0
4
Order By: Relevance
“…In this sense, the findings of this study add to previous research that shows how assessment and grading is based on criteria not found in the curriculum (e.g. Harris & Leggett, 2015;Michael et al, 2016;Borghouts et al, 2017) which in this case involves 'being good at the right sports'.…”
Section: Discussionsupporting
confidence: 72%
“…In this sense, the findings of this study add to previous research that shows how assessment and grading is based on criteria not found in the curriculum (e.g. Harris & Leggett, 2015;Michael et al, 2016;Borghouts et al, 2017) which in this case involves 'being good at the right sports'.…”
Section: Discussionsupporting
confidence: 72%
“…Providing professional development for teachers is essential and several studies have proved so (Colwell et. al., 2014;Haag & Megowan, 2015: Micheal, et al, 2016Tondeur, et al, 2016;Sibert, & Rieg, 2016). However, identifying, the right professional development is critical.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…If teachers have difficulty communicating what knowledge and abilities the students should learn, it is likely that the subject's curriculum goals do not form the basis for the assessment of the students and there is a risk that the students focus on what is assessed instead of the achievement objectives in the PEH curriculum (Redelius and Hay, 2009). Indeed, there appears to be a misalignment in PEH (Coulter et al, 2020) between curriculum objectives and assessment practice whereby knowledge and abilities are being assessed that are beyond the scope of the official curriculum (Borghouts et al, 2017; Harris and Leggett, 2015; Michael et al, 2016; Modell and Gerdin, 2021).…”
Section: Perceptions Of Peh and Assessmentmentioning
confidence: 99%